INITIATION OF DESIGN AND MANUFACTURE OF BATIK WASTE RECEPTACLES FOR THE SARIWARNI BATIK GROUP IN MADIUN REGENCY - Isnaini, Wildanul; Nisa, Nur Ihda Farikhatin; Setiawan, Dimas (Journal of Islam and Science, 2019)
Sariawarni Batik Group is one of the batik groups in Madiun Regency that is classified as successful in marketing their products. Sariwarni Batik Group is chaired by Mrs. Siti Suwarni and consists of 14 people who are housewives. Sariwarni Batik Group produces several types of batik,i.e. written batik, stamp, and ecoprint. Until now, Sariwarni batik group still uses synthetic dyes in its production. This study aims to create a waste disposal design that will be tailored to the needs of the Sariwarni batik group and adjusted for the cost and time available. As a result, the design of the wastewater collection tank in the Sariwarni Batik Group has been completed and can be used. With this tub, the Batik Sariwarni Group does not need to dispose of batik liquid waste into the yard of the house. In addition, the reservoir can separate and precipitate wax, oil and other particles.